Hecate in Plutarch - López-Carrasco, Nerea (My University, 2018)
This paper studies the Plutarchean conception of Hecate from a selection of passages where the name of the goddess is explicitly mentioned and which belong to the three fields of Plutarch’s works: Astrology, Religion (including Mysteries) and Magic. I will show the thematic interconnection between them having Hecate as common thread. This way, we will see the associations between Hecate and different divinities (especially Selene) in each field, as well as the particular epithets applied to the goddess (χθονία, φωσφόρος, Τριοδῖτις, οὐρανία…) which sometimes reveal or depend on such associations. Finally, some further considerations will be made about the Mystery profile of Hecate in Plutarch and its relation with Astrology.
Hécate en Plutarco
Keywords: Plutarco - Crítica e interpretación; Hecate; Plutarch; Epithets